From Ancient Mythology to Modern Technology: The Historical Evolution of Artificial Intelligence - Duymaz, Yaşar Kemal; Şahin, Şamil (European Journal of Therapeutics, 2023)
Dear Editors, Recently, a fascinating article detailing the evolution of Artificial Intelligence (AI) was published, as the article describes it with the bronze creature Talos from ancient Greek myths and the groundbreaking DaVinci Si and DaVinci Xi surgical systems of the modern era [1]. The interaction of ancient myths and medical technology shows how far we have come but how deeply we remain connected to our past. As the article emphasizes, Talos, described in ancient Greek literature, may be the world's first recorded concept of an automaton with Artificial Intelligence capability. Talos, created by the god Hephaestus, used his bronze form and inner fire to patrol the coasts of Crete and deter invaders [2]. The story of a machine that moves independently, driven by an energy source and following specific instructions, is astoundingly pioneering [2]. It is interesting to think that robots, an idea we usually think of as a modern concept, were present in the imagination of ancient civilizations. Leonardo da Vinci's robot knight is a moving tribute to the versatile genius of the Renaissance [3]. However, since its operation depends on external intelligence, it is not a direct precursor to the AI we know today. The article makes this distinction. However, A claim that has been presented is open to discussion. Naming AI surgical tower da Vinci is misleading, article suggests. Although Leonardo's automaton was not autonomous, its extensive notebooks testify to a questioning and innovative mind that was always pushing boundaries. In this sense, it feels appropriate to mention the name of Da Vinci, a technological marvel. The underlying sentiment is concurred with. Hephaestus' creation of Talos offers a more direct line to the concept of autonomous machines and perhaps it deserves a more prominent position in the story of the history of Artificial Intelligence. Highlighting this overlooked intersection of mythology, history, and technology is commendable. Such discussions highlight the importance of understanding our past while understanding our rapidly evolving present and future. Sincerely yours,